2019
DOI: 10.1051/0004-6361/201936117
|View full text |Cite
|
Sign up to set email alerts
|

Survey of asteroids in retrograde mean motion resonances with planets

Abstract: Aims. Asteroids in mean motion resonances (MMRs) with planets are common in the solar system. In recent years, increasingly more retrograde asteroids are discovered, several of which are identified to be in resonances with planets. We here systematically present the retrograde resonant configurations where all the asteroids are trapped with any of the eight planets and evaluate their resonant condition. We also discuss a possible production mechanism of retrograde centaurs and dynamical lifetimes of all the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…3 shows a temporal density plot of the S1 clones according to their average time spent in a particular orbit. Objects that reach a moderate-to-low-eccentricity, polar orbit have higher average lifetimes than objects that remain retrograde close to the ecliptic (also see Gallardo 2019;Li et al 2019). Correspondingly, these objects appear as darker shades of green in the density plot.…”
Section: Backpropagation Of Ka'epaoka'awelamentioning
confidence: 97%
See 1 more Smart Citation
“…3 shows a temporal density plot of the S1 clones according to their average time spent in a particular orbit. Objects that reach a moderate-to-low-eccentricity, polar orbit have higher average lifetimes than objects that remain retrograde close to the ecliptic (also see Gallardo 2019;Li et al 2019). Correspondingly, these objects appear as darker shades of green in the density plot.…”
Section: Backpropagation Of Ka'epaoka'awelamentioning
confidence: 97%
“…Some objects even flip to prograde motion in the presence of giant planets (e.g. Lithwick and Naoz 2011; Greenstreet et al 2012;Li et al 2019). This leads to what essentially constitutes a selection process that filters out the short-lived particles.…”
Section: Backpropagation Of Ka'epaoka'awelamentioning
confidence: 99%
“…One year later, Morais & Namouni (2017) identified that 2011 KT19 is currently inside a 7:9 polar resonance with Neptune. In a recent survey of retrograde asteroids performed by Li et al (2019), the authors confirmed that 2011 KT19 is currently in a retrograde 7:9 resonance with Neptune.…”
Section: Introductionmentioning
confidence: 92%
“…According to Morais & Namouni (2013a) and Li et al (2019), it is known that asteroids 2008 SO218 and 1999 LE31 are currently inside the retrograde 1:2 resonance with Jupiter. For convenience, we mark their locations in the (a, e) space, as shown in Fig.…”
Section: Numerical Widths Over the Full Range Of Eccentricitymentioning
confidence: 99%
See 1 more Smart Citation